The impact of puffball autolysis on selected chemical and biological properties: puffball extracts as potential ingredients of skin-care products - Petrović, Predrag; Ivanović, Katarina; Jovanović, Aleksandra; Simović, Milica; Milutinović, Violeta; Kozarski, Maja; Petković, Miloš; Cvetković, Anka; Klaus, Anita; Bugarski, Branko (Archives of Biological Sciences, 2019)
Paper description: Mature puffballs have been used in traditional medicine as haemostyptics. Methanol extracts of young and mature fruiting bodies of Handkea excipuliformis and Vascellum pratense were subjected to chemical analysis, with accent on the compounds involved in skin care and regeneration, and screened for their antioxidant, tyrosinase-inhibitory and antimicrobial activities which could have a role in treatments of various skin conditions. Mature fruiting body extracts are generally richer in N-acetylglucosamine, phenolics, α-tocopherol, ergosterol, linoleic acid and exhibited better antioxidant and tyrosinase-inhibitory activities. Mature puffballs can be used as ingredients in medical and cosmetic skin products. Abstract: Puffballs are fungi that produce globose fruiting bodies that undergo autolysis, transforming their insides into a spore bearing, powdery mass. Mature fruiting bodies are traditionally used to treat open skin wounds. In this study, methanol extracts of two puffball species, Handkea excipuliformis and Vascellum pratense, were examined and compared in order to provide insight into the changes these mushrooms undergo during maturation, with respect to their potential use in skin care and wound treatment. Some compounds involved in skin care and regeneration were quantified, and it was found that maturation increases the concentrations of almost all of these compounds. Antioxidant activity was also more pronounced in mature fruiting body extracts, which was in correlation with the higher content of antioxidants. Tyrosinase inhibition was vastly improved with autolysis, correlating with the higher phenolic content in mature fruiting body extracts. Antimicrobial activity was negatively affected by autolysis in the case of H. excipuliformis, whereas autolysis had little effect on the antimicrobial activity of V. pratense. Autolysis generally improved the biological activity and increased the concentrations of compounds involved in skin care, which justifies the traditional use of puffballs and makes them good candidates for various potential cosmetic and medicinal skin-care products. https://doi.org/10.2298/ABS190725055P Received: July 25, 2019; Revised: August 26, 2019; Accepted: August 28, 2019; Published online: September 5, 2019 How to cite this article: Petrović P, Ivanović K, Jovanović A, Simović M, Milutinović V, Kozarski M, Petković M, Cvetković A, Klaus A, Bugarski B. The impact of puffball autolysis on selected chemical and biological properties: Puffball extracts as potential ingredients of skin-care products. Arch Biol Sci. 2019;71(4):721-33.